Blow up for a Nonlinear Viscoelastic Wave Equation with Strong Damping, Source and Delay Termes - Choucha, Abdelbaki; Ouchenane, Djemal (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, we are concerned with a problem for a nonlinear viscoelastic wave equation with strong damping, source and delay terms, we proved a blow up result for the solution with negative initial energy under suitable conditions.